Proteomic Profiling of Exosomes Secreted by Breast Cancer Cells with Varying Metastatic Potential. Issue 23 (20th December 2017) - Gangoda, Lahiru; Liem, Michael; Ang, Ching‐Seng; Keerthikumar, Shivakumar; Adda, Christopher G.; Parker, Belinda S.; Mathivanan, Suresh
Abstract: Cancer cells actively release extracellular vesicles, including exosomes, into the surrounding microenvironment. Exosomes play pleiotropic roles in cancer progression and metastasis, including invasion, angiogenesis, and immune modulation. However, the proteome profile of exosomes isolated from cells with different metastatic potential and the role of these exosomes in driving metastasis remains unclear. Here, we conduct a comparative proteomic analysis of exosomes isolated from several genetically related mouse breast tumor lines with different metastatic propensity. The amount of exosomes produced and the extent of cancer‐associated protein cargo vary significantly between nonmetastatic and metastatic cell‐derived exosomes. Metastatic cell‐derived exosomes contain proteins that promote migration, proliferation, invasion, and angiogenesis while the nonmetastatic cell‐derived exosomes contain proteins involved in cell–cell/cell–matrix adhesion and polarity maintenance. The metastatic exosomes contain a distinct set of membrane proteins including Ceruloplasmin and Metadherin which could presumably aid in targeting the primary cancer cells to specific metastatic sites. Hence, it can be concluded that the exosomes contain different protein cargo based on the host cells metastatic properties and can facilitate in the dissemination of the primary tumors to distant sites.